Prevalence, Mortality, and Associated Anomalies in Esophageal Atresia: A Retrospective Study of Finnish Population Data (2004–2017) - Alikärri, Suvi; Helenius, Ilkka; Heiskanen, Susanna; Syvänen, Johanna; Kemppainen, Teemu; Löyttyniemi, Eliisa; Gissler, Mika; Raitio, Arimatias (European Journal of Pediatric Surgery, 2024)
Introduction The aim of the study was to investigate the prevalence of esophageal atresia (EA), frequency of associated anomalies, and mortality from 2004 to 2017 in the Finnish population. We hypothesized the Spitz classification and the presence of other congenital malformations would predict mortality in patients with EA as well as assumed the survival to be high among patients with EA.Materials and Methods This retrospective, population-based study was based on the registries maintained by THL Finnish Institute for Health and Welfare and Statistics Finland. The cases were identified and classified according to the World Health Organization's International Classification of Diseases and Health Related Problems (ICD) revisions 9 and 10 (ICD-9 and ICD-10) codes and accompanying written diagnoses. Associated anomalies were classified based on the EUROCAT criteria, and minor anomalies were excluded. All statistical tests were performed as a two-sided significance level set at p < 0.05. The chi-square or Fisher's exact test was utilized for categorical variables. The change in prevalence rates during the study period was evaluated with linear regression.Results In total, 337 cases with EA were identified including 295 (87.5%) live births, 17 (5.0%) stillbirths, and 25 (7.4%) terminations of pregnancy. The total prevalence for EA in Finland was 4.17/10,000 births with no significant change during the study period, p = 0.35. Neonatal mortality was 5% (n = 15) and 1-year survival was 91.5%. Mortality was associated with syndromic cases (p = 0.002). The Spitz classification predicted neonatal mortality better than cardiac anomalies alone (p < 0.001 and p = 0.6, respectively). Type C was the most common atresia type (65.9%) followed by type A (14.8%) and B (6.8%). The most common group of associated malformations were heart defects (35.0%) followed by other gastrointestinal tract malformations (15.3%) and limb anomalies (12.2%). Syndromic cases (12.2%) were associated with type A and B atresias (p = 0.001). VACTERL association was observed in 16.6% of the cases.Conclusion The overall prevalence of EA remains stable and relatively high in Finland. Despite the high prevalence of co-occurring malformations, the overall survival rate is high. Spitz classification predicted neonatal survival well.
Keywords: esophageal atresia; prevalence; mortality; associated anomalies; Spitz classification